Migration and Productivity in the UK: An Analysis of Employee Payroll Data - Hoseong Nam; Jonathan Portes (Institute of Labor Economics (IZA), 2023)
We investigate the impact of immigration on productivity in the UK, using newly published ONS data on employees of non-UK origin by region and sector. Consistent with earlier research, we find some evidence of a positive association between non-EU migration and productivity, and some weaker evidence of a negative association between EU migration and productivity, although results are sensitive to the specifications used.
Keywords: F22; J48; J61; J68; 330; migration; productivity; labour markets; Brexit